2018
DOI: 10.1136/jclinpath-2018-205000
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Hsp27 is mutually exclusive with ATRX loss and the IDH1R132Hmutation and may predict better prognosis among glioblastomas without the IDH1 mutation and ATRX loss

Abstract: AimTo identify biomarkers for accurate classification of glioma.Patients and methodsWe evaluated the heat shock protein 27 (Hsp27), phosphorylated Hsp27 (p-Hsp27), ATRX and IDH1R132Hproteins using immunohistochemistry in 421 glioma tissues. The χ2 test was used to assess the relationship between molecular alterations and clinico-pathological parameters. Kaplan-Meie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…A previous study reported the clinical relevance of IDH1 mutation in gliomas (28). In the present study, it was observed that patients with IDH1 mutation showed favorable prognosis (P= 0.048; Fig.…”
Section: Using Skp2 Idh1 Mutation and Tert Promoter Mutation Data CLsupporting
confidence: 69%
“…A previous study reported the clinical relevance of IDH1 mutation in gliomas (28). In the present study, it was observed that patients with IDH1 mutation showed favorable prognosis (P= 0.048; Fig.…”
Section: Using Skp2 Idh1 Mutation and Tert Promoter Mutation Data CLsupporting
confidence: 69%
“…For the same cases, we previously reported high expression of Hsp27 protein and isocitrate dehydrogenase 1 (IDH1) mutation in tumors [22]. In the present study, we further investigated TERTp mutation, and simultaneously analyzed the relationship between IGFBP2 mRNA expression and the alterations of TERTp, Hsp27 and IDH1 (Figure 2).…”
Section: Resultsmentioning
confidence: 69%
“…The following antibodies were used: anti-heat shock protein 27 (Hsp27) antibody (1:500, 50353, CST), anti-IDH1 R132H antibody (working solution, ZM0447, ZSGB-BIO). The immuno-scores for these antibodies were evaluated as previously described [22].…”
Section: Methodsmentioning
confidence: 99%
“…TMAs and paraffin-embedded subcutaneous xenograft were cut into 5-μm sections. Immunohistochemistry and evaluation of immunostaining were performed as described previously [ 22 ]. The following primary antibodies were used: anti-FKBP10 antibody (1:2000, 50353, Sigma), anti-Hsp47 antibody (1:1200, sc5293, Santa Cruz), anti- p-CREB (1:1000, 9198S, CST) and PCNA (1:5000, 13110S, CST).…”
Section: Methodsmentioning
confidence: 99%